(untitled) (Human Computation, 2016)
The development of the geospatial web (GeoWeb) over the past decade opened up opportunities for collaborative mapping and large scale data collection at unprecedented scales. Projects such as OpenStreetMap, which engage hundreds of thousands of volunteers in different aspects of mapping physical and human-made objects, to eBird, which records millions of bird observations from across the globe. While these collaborative mapping efforts are impressive in their scale and reach, there is another type of mapping which is localised, frequently carried out over a limited period of time, and aims at solving a specific issue that the people who are living in the locality are facing. These needs are addressed in participatory mapping, which nowadays includes citizen science elements in data collection and management. The paper describes the background and design of a novel infrastructure for participatory mapping and science – GeoKey. The paper provides a differentiation between collaborative and participatory mapping, describes the state of the art and several use cases of community mapping, and the architecture of GeoKey, focussing both on the approaches to data capture and subsequent potential to share the data in an open manner where possible. It also describes the design elements that support learning and creativity in these projects